Comparative study of the effect of "Ginger-Lavender" capsule with "Mefenamic Acid" on the severity of primary dysmenorrhea: A randomized clinical trial - Shadi Ahmadi; Sharareh Jannesari; Maliheh Nasiri; Shamim Sahranavard (Mashhad University of Medical Sciences, 2022)
Introduction: Dysmenorrhea‌ is a‌ major problem‌ in women's‌ general and ‌individual health. Complications of nonsteroidal anti-inflammatory drugs (NSAIDs) in this disease have led to an increase in the tendency to complementary, alternative and herbal remedies. ‌This study was performed with aim to compare the effect of‌ "Ginger-Lavender"‌ capsule with" Mefenamic Acid"‌ on the severity of primary dysmenorrhea.  Methods: This triple-blind clinical trial study was conducted in in 2020 on 60 students with a history of primary dysmenorrhea living in the selected dormitories of Shahid Beheshti University of Medical Sciences. The research tools were the questionnaire of menstrual status, demographic and anthropometric characteristics form and pain line. In the intervention group, Ginger-Lavender capsules and in the control group, Mefenamic Acid capsules were prescribed four times daily for 3 days from the onset of menstruation bleeding. Pain intensity was measured during 2 months. Data were analyzed by SPSS software (version 24) and independent t-test,‌ Bonferroni, Fisher, and Analysis of Variance. P<0.05 was considered statistically significant. Results: Before the intervention, there was no significant difference between the groups in terms of pain intensity ‌(p‌=‌0.22). Intergroup comparison in three cycles using two-factor analysis of variance showed a statistically significant difference between the two groups of ginger-lavender and mefenamic acid in terms of pain intensity (p = 0.01). The mean pain score in the ginger-lavender capsule group was 1.53 less than the mefenamic acid capsule group. There was a significant difference in the ginger-lavender group in the duration and severity of bleeding compared to the three cycles (p = 0.04 and P = 0.03), respectively). Conclusion: The Ginger-Lavender‌ capsule without any side effects reduces the pain of primary dysmenorrhea and is more effective than Mefenamic Acid. Ginger-lavender capsule can be used as an effective herbal medicine without side effects in reducing dysmenorrhea pain.